Upaya dalam Meningkatkan Loyalitas Kerja Karyawan dan Implikasinya terhadap Produktivitas pada PT. Bank Pembangunan Daerah Jambi - Dea Anugrah Putri; Zulfina Adriani; Wahyu Juari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Employee loyalty is an important factor in the sustainability and productivity of a company. This research aims to analyze the efforts made by PT. Jambi Regional Development Bank in increasing employee loyalty and its implications for company productivity.The research method used is a qualitative method. Data was collected through interviews with employees of the credit division of PT. Jambi Regional Development Bank and documentation studies. The research results show that there is a positive and significant relationship between efforts to increase employee loyalty and company productivity. Factors such as increased welfare, career development, a conducive work environment, and effective internal communication play an important role in increasing employee loyalty. The higher the level of employee loyalty, the higher the level of productivity achieved by the company. The implication of this research is that companies need to continue to develop strategies to maintain and increase employee loyalty in order to achieve optimal levels of productivity. The recommendations provided include improving the incentive system, increasing employee involvement in decision making, and providing ongoing training programs.